Recensión de Frédérique Michèle Rey – Eric D. Reymond, A Critical Edition of the Hebrew Manus- cripts of Ben Sira. With Translations and Philological Notes (Supplements to the Journal for the Study of Judaism 217; Brill, Leiden – Boston 2024). xxx + 322 p - Carbajosa, Ignacio (Estudios bíblicos, 2025)
Publicación cuatrimestral de referencia internacional en estudios bíblicos, editada por la Universidad San Dámaso en colaboración con la Asociación Bíblica Española.